USING DIALOGIC TEACHING IN IMPROVING STUDENTS’ ENGLISH-SPEAKING SKILLS AT UPT SMAN 14 MAROS - Lindi La Uni; Jusmaniar N; Dahniar Dahniar (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
This research aims to investigate the use of Dialogic Teaching in improving the students' speaking skills by applying the five basic principles of Dialogic Teaching: Collective, Reciprocal, Supportive, Cumulative, and Purposeful, as well as implementing two patterns of Dialogic Teaching interaction in the speaking learning process: Discussion and Dialogue. A quasi-experimental design was used in this research, which took two classes as samples, namely second grade MIA 1 as an experimental class, taught through a Dialogic Teaching approach, and second grade MIA 2 as a control class as the opposite. Pre-test and post-test were used to assess the students' English-speaking skills; and was analyzed quantitatively. The research results showed that the use of Dialogic Teaching improves students’ speaking skills. It was proven by the mean score of pre-test and post-test of Experimental class were 48 and 67.07 respectively, which categorized as Less and Good. While in Control class, it got the Less and Enough categories with 47.87 and 56 respectively. The T-test value was 0.000 that it was lower than the probability value: 0.05. Therefore, it could be concluded that Hi was accepted and Ho was rejected, which meant that the use of Dialogic Teaching in the learning process, it could improve the students' English speaking skills.